The ontological question in the instrumentalist conception of law / Mohd Darbi Hashim - Hashim, Mohd Darbi (Faculty of Administratron and Law, 2001)
The particular point in question which the report has raised and which will be taken up for discussion in this article is the evident realization at the highest level by the country's powers-that-be regarding law's efficacy as a tool or instrument for development and economic policy. In Malaysia such a view toward law is rather unconventional, because the general attitude among legal practitioners and lay public alike is that law is no more than a means of social control for the preservation of the social order and a framework for "conflict amelioration"